Interaction of 5-amino-1,3,4-thiadiazole-2-thiol and its Violuric Acid Adduct with Pt(II) – Crystals Structures, Spectroscopic Properties and Cytotoxic Activity - Kavlakova, M.; Bakalova, A.; Momekov, G.; Ivanov, D. (Arzneimittelforschung, 2012)
The coordination properties of Pt(II) with 5-amino-1,3,4-thiadiazole-2-thiol [CAS 2349-67-9] (L1) and its novel violurate adduct (L2), both in solution and in solid state, are studied by means of conventional IR-spectroscopy, single crystal X-ray diffraction and thermal methods. The complex compounds of L1 and L2, with general formulas [Pt(C2H2N3S2)2] and [Pt(C6H4N6S2O3)(Cl)]Cl respectively, are obtained. Quantum chemical calculations of the ligands are performed with a view to obtain electronic structure and optical properties of the ligands L1 and L2, respectively. The cell viability of the ligands and metal complexes on a panel of human tumor cell lines is evaluated.
Keywords: 5-amino-1,3,4-thiadiazole; violurate adduct; Pt (II) complexes; spectroscopic and structural elucidation; cytotoxic activity